Exposure to mass media and interpersonal counseling has additive effects on exclusive breastfeeding and its psychosocial determinants among Vietnamese mothers - Nguyen, Phuong Hong; Kim, Sunny S.; Nguyen, Tuan T.; Hajeebhoy, Nemat; Tran, Lan Mai; Alayon, Silvia; Ruel, Marie T.; Rawat, Rahul; Frongillo, Edward A.; Menon, Purnima (Wiley, 2016)
The pathways through which behavior change interventions impact breastfeeding practices have not been well studied. This study aimed to examine: (1) the effects of exposure to mass media and interpersonal counseling on exclusive breastfeeding (EBF) and hypothesized psychosocial determinants (i.e. knowledge, intention, beliefs, social norms, and self‐efficacy); and (2) the pathways through which exposure to mass media and interpersonal counseling are associated with EBF. We used survey data from mothers with children < 2 year (n = 2045) from the 2013 process evaluation of Alive & Thrive's program in Viet Nam. Multiple linear regression analyses and structural equation modeling were used to estimate effects. Exposure to mass media only, interpersonal counseling only, both or neither was 51%, 5%, 19% and 25%, respectively. Exposure to both mass media and interpersonal counseling had additive effects on EBF as well as on related psychosocial factors, compared with no exposure. For example, EBF prevalence was 26.1 percentage points (pp) higher in the group that received interpersonal counseling only, 3.9 pp higher in the mass media group and 31.8 pp higher in the group that received both interventions. As hypothesized, more than 90% of the total effect of the two interventions on EBF was explained by the psychosocial factors measured. Our findings suggest that combining different behavior change interventions leads to greater changes in psychosocial factors, which in turn positively affects breastfeeding behaviors.